Measurement and evaluation of the coupling degree between National Fitness and National Health in the Yangtze River Economic Belt region of China - Cai, Changwen; Ye, Songzhong (Frontiers in Public Health, 2023)
Clarifying the integrated development mechanism of the National Fitness Program and National Health Program has positive and practical significance for the efficient implementation of the healthy China strategy. In order to analyze and study the integrated development mechanism of the National Fitness Program and National Health Program, we established a coupling-coordination measurement model. Based on two dimensions of space and time, we first analyzed the coupling degree between National Fitness System and National Health System in the Yangtze River Economic Belt region of China from 2016 to 2020, and studied and analyzed the coupling mechanism between the two. The research results show that the National Fitness Program and National Health Program have a development model of mutual promotion and mutual benefit. The National Fitness Program promotes the National Health Program by improving the fitness environment, increasing fitness participation, and health investment. The National Health Program optimizes environmental construction, health education, and healthy populations, thereby driving national fitness. Overall, there is stable development and balanced promotion in the integration of the National Fitness Program and National Health Program. In addition, the integrated development of the National Fitness Program and National Health Program is positively affected by economic level and regional marketization. The coupling- coordination model adopted in this study has practical value in measuring the coupling degree between the National Fitness System and National Health System. The results of this study also provide an important reference basis for the integrated and coordinated development of the National Fitness Program and National Health Program and the implementation of the Healthy China strategy.